Guanine-1,N6-ethenoadenine base pairs in the crystal structure of d(CGCGAATT(epsilon dA)GCG). - Leonard, G; McAuley-Hecht, K; Gibson, N; Brown, T; Watson, W; Hunter, W (1994)
A single-crystal X-ray analysis of the synthetic oligomer d(CGCGAATT(epsilon dA)GCG) (epsilon dA = 1,N6-ethenoadenosine) has been carried out. The B-form duplex crystallizes in the orthorhombic space group P2(1)2(1)2(1) with unit cell dimensions a = 24.31 A, b = 39.65 A, and c = 63.05 A. Refinement has converged with R = 0.182 for 2837 reflections in the resolution range 7.0-2.25 A for a model consisting of the duplex, one Mg2+ ion, and 127 water molecules. The structure contains two G.epsilon dA base pairings which adopt a G(anti).epsilon dA(syn) conformation. The geometry of the two mispairs suggests that the G.epsilon dA pairing are held together by three interbase hydrogen bonds. These are N2(G)-H...N1(epsilon dA), N1(G)...N9(epsilon dA), and O6(G)...H-C8(epsilon dA). The last interaction serves to alleviate the destabilizing effect that would occur due to the presence of an unfulfilled hydrogen bond acceptor. A superposition of the G(4).epsilon dA-(21) base pair found in this structure and the Watson-Crick G(4).C(21) base pair observed in the native dodecamer d(CGCGAATTCGCG) indicates a significant difference in the sugar/phosphate backbone. However, the overall conformations of the two duplexes remain similar, suggesting that the modified base pairs are accommodated into the double helix mainly by alterations of the backbone conformation. Such structural rearrangement of the backbone, upon incorporation of epsilon dA, may provide a signal to the 3-methyladenine-DNA glycosylase that repairs such lesions.